PHENOMENAL FORMS OF FRAUD IN SYSTEM OF INDIRECT TAXATION - Elvir Sačić (Human Research in Rehabilitation, 2011)
This work could be summarized by unique description: it is phenomenological analysis designed to determine and analyze the concept of crimes against financial interests, i.e. budgetary funds of Bosnia and Herzegovina as well as of the European Union. Through a syn- thetic and casuistic description of individual phenomenological forms of criminal actions and the systematisation of them according to given criminological characteristics, an endeavour is made to delve into the complex fiscal, financial, economic and legal context in which these deeds arise, and to associate them more closely with the practical reality. In order to bring to light the multidimensional importance and throw light on crime against the budget of the Bosnia and Herzegovina and the EU from several aspects, in this paper a phenomenological analysis is carried out at several levels and is based on main criteria: the phenomenological forms considering the kind of legally protected good – the revenues and/or expendituresof the budget.